Republic of Armenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
Although Armenia itself has a population of only about 3 million, an estimated 8 million Armenians live abroad. In this paper, the size and the sources of remittances to Armenia are first discussed. Then, the appropriate definition of remittances and subsequently present estimates of the macroeconomic effects of remittances to Armenia are outlined. Remittances play a significant role in the Armenian economy. They amount to between USD 250 million and USD 1 billion per year, and constitute from 25 percent to 80 percent of remittance receivers' incomes.